POLÍTICAS DE DESENVOLVIMENTO E DESCENTRALIZAÇÃO DO PARANÁ: UM ESTUDO SOBRE APL CAL E CALCARIO DA RMC - Silva, Christian Luiz da; Farah Jr, Moises Francisco; Meza, Maria Lucia Figueiredo de Gomes; Muniz, Sérgio Tadeu Gonçalves; Oliveira, Antonio Gonçalves (Informe GEPEC, 2010)